Effect of Delayed Icing on the Microbiological Quality of Hilsa Toli - A., Ramachandran; Badonia, Rajendra; P.G., Viswanathan Nair (Fishery Technology, 2025)
Effect of delayed icing on the microbial quality and shelf-life of Hilsa toli was stu- died. Fish iced in rigor condition had a shelf-life of 11 days irrespective of the state of rigor. Fish procured from the landing centre had a shelf-life of only 8 days. It showed the presence of coagulase positive staphylococci, faecal streptococci and E. coli. Total bacterial count was low in all the samples and it increased after spoilage.